VD_FINDINFO Pron / 2018 / 9 vom 5. Juli 2018 - VD Tribunal cantonal (2018)
SÛRETÉS, CONSORITÉ, INTÉRÊT JURIDIQUEPROCÉDURE CIVILE | 106 al. 1 CPC (CH), 106 al. 3 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. a CPC (CH), 71 CPC (CH), 99 al. 1 CPC (CH)